Ancient and methane-derived carbon subsidizes contemporary food webs - Amanda G. DelVecchia (Nature Portfolio, 2016)
Alluvial aquifers of river floodplains support abundant large-bodied consumers despite an absence of light and scarcity of organic carbon. DelVecchia et al. reveal that much of the biomass carbon in these freshwater consumers is ancient and derived from methane.